Potensi Pengembangan Circulamodo untuk Meningkatkan Keaktifan Peserta Didik - Berti Priska Gea; Indah Pratiwi; Silvani Mursida Damanik; Satri Dwi Kurnia; Rizhal Hendi Ristanto; Mieke Miarsyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to develop Circulamodo learning media in increasing the active potential of students. The research method used is the ADDIE development method through analysis, design, development, implementation, and evaluation stages. The results showed that 1) the average score of Circulamodo's media assessment was 77.4% and had good qualifications; 2) the active potential of students is 76% and is categorized as very good; 3) students' cognitive learning outcomes increased by 39.8%. In conclusion, the development of Circulamodo media is proven to increase student activity potential. Keywords: ADDIE, Cognitive Learning Outcomes, Circulamodo Media, Activity Potential